A protocol for a scoping review of variations among psychedelic interventions for psychological suffering associated with the end-of-life - Sarah Kratina; Carol Strike; Robert Schwartz; Ayah Nayfeh; Sydney Jopling; Chris Lo; Brian Rush (PLoS ONE, 2025)
Psychedelic substances are increasingly recognized for their therapeutic potential to ease psychological suffering linked to end-of-life issues. However, amid renewed scientific and public interest, policy remains restrictive. Existing reviews have made progress in synthesizing the results of studies of psychedelic interventions, especially psilocybin, and particularly with regard to their outcomes related to anxiety and depression, long-term effects and safety. Despite this progress, a wide range of both substances (such as ayahuasca, psilocybin, ketamine) and therapeutic approaches (such as psychedelics alone, or psychotherapy assisted with a psychedelic) in the use of psychedelic interventions specifically for end-of-life populations, has not been adequately covered by reviews to date. The aim of this scoping review is to identify and learn from the variety of psychedelic substances and therapeutic approaches that exists within the research on therapeutic psychedelic interventions reported in populations coping with psychological suffering associated with life-threatening illness and the end of life itself. We will follow Arksey and O’Malley’s (2005) framework for scoping reviews while incorporating updated methodological guidance. The Preferred Reporting Items for Systematic Review and Meta-Analyses extension for scoping reviews (PRISMA-ScR) guideline will be used to organize the search and identification of research focusing on psychedelic interventions, psychological suffering, and end-of-life issues. Health science databases such as Medline, Embase, APA PsychINFO, and CINAHL will be searched. The search will be limited to empirical published data on ‘end-of-life’, ‘psychedelics’, and ‘psychological suffering’. Data extracted from selected studies will cover intervention details, participant characteristics, measured outcomes, and theorised mechanisms. The insights gained from this review will be used to inform future research and discussions on how psychedelics can be integrated into care strategies for populations coping with end-of-life concerns. This scoping review does not require ethics approval.